Analysis Of The Indonesian National Police’s Merit-Based Assessment Center For The Position Of Head Of Society Guidence Section At The Central Java Regional Police - Guntur Wahyu Setyawan; Andreo Wahyudi Atmoko (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The transformation of public sector human resource management requires the implementation of an objective and professional merit-based system; however, its implementation in Indonesia—particularly regarding the use of Assessment Centers—still faces various challenges. This study aims to analyze the implementation of a merit-based Assessment Center in the selection process for the position of Head of Community Relations (Kasat Binmas) at the Central Java Regional Police Headquarters and to identify the factors influencing it. The study employs a descriptive qualitative approach through a literature review of relevant scientific sources and policy documents. The results indicate that, normatively, the Assessment Center has been conducted in accordance with meritocratic principles using comprehensive instruments; however, empirically, its effectiveness remains suboptimal, marked by a predominance of candidates in the intermediate competency category and a scarcity of candidates with outstanding qualifications. Major obstacles include low applicant interest, budget constraints, low assessor capacity, limited digital literacy among candidates, as well as potential bias and interference in the selection process. The implications of this study underscore the need for institutional capacity building, enhanced human resource competencies, and the optimization of transparent and accountable governance to realize an effective and sustainable merit-based system in the management of the Indonesian National Police’s human resources.